Practical Rhetoric - Hardison, O.B. Jr. (New York Appleton Century Crofts, 1966)
The purpose of this book is to teach effective writing skills. Throughout life, everyone encounters times of difficulty in expression and having good writing skills will help to overcome this.
Keywords: Writing